Learning the Course of Design and Analyze of Computer Algorithms via Online Coding - Jianwei Liao; Xiaoyan Liu (International Journal of Evaluation and Research in Education (IJERE), 2013)
The course of design and analysis of computer algorithms is one of the core-course of computer science education; this paper presents an online coding framework to help students to learn the course of design and ananlysis of computer algorithms and other coding-related courses in computer science. With the online coding framework, a student can edit code in any web browser, and then executes it. This online coding framework can connect teachers, curriculum authors, and students in a unique social experience by tracking and streaming progress updates in real time. In particular, with the newly proposed framework, it is not difficult to find interesting and unexpected input values during students’practicing, and then help them to understand what their code is actually doing.DOI: http://dx.doi.org/10.11591/ijere.v2i3.2570